2020
DOI: 10.1177/0033354920921252
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the Rights of Health Care Students Living With Hepatitis B Under the Americans With Disabilities Act

Abstract: 14S to ensure that persons living with HBV infection have the opportunity to study and pursue careers in the health professions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The new data from this study suggest that a functional cure would alleviate this fear and anxiety associated with the risk of transmission to others and potential complications including cirrhosis and reduced risk of liver cancer, which in turn would improve overall quality of life. Additionally, stigma and discrimination among those with HBV infection are common worldwide, including in the United States 17‐22 . HBV‐related stigma can lead to social and emotional isolation, and HBV‐related discrimination can limit employment and educational opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…The new data from this study suggest that a functional cure would alleviate this fear and anxiety associated with the risk of transmission to others and potential complications including cirrhosis and reduced risk of liver cancer, which in turn would improve overall quality of life. Additionally, stigma and discrimination among those with HBV infection are common worldwide, including in the United States 17‐22 . HBV‐related stigma can lead to social and emotional isolation, and HBV‐related discrimination can limit employment and educational opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…10,14 Even with protections and policy in place, refusal of admission within nursing and medical schools still is reported to occur. 14 There is a need to systematically document discrimination at local, country, regional and global levels and which should include the location, the causes of discrimination, where and how it is occurring at a local level. This documentation could be used to inform policy that ensures people with hepatitis B are provided protection and equal opportunity for employment, education, travel and immigration.…”
Section: Discussionmentioning
confidence: 99%
“…13 In the U.S., discrimination is experienced by healthcare students, causing denial of school admission or enrollment, restriction of clinical training or dismissal from an academic program. 14 While hepatitis B discrimination has largely been reported anecdotally within a global context, this study aims to investigate and describe hepatitis B related discrimination, document discrimination occurring around the globe, and provide initial recommendations for addressing discrimination using key informant interviews. For the purposes of this study, discrimination is described by modifying the HIV-speci c discrimination de nitions within the United Nations, 15 and where discrimination speci c to hepatitis B is de ned as the unjust, unfair, or prejudicial treatment of a person on the grounds of their hepatitis B status.…”
Section: Introductionmentioning
confidence: 99%
“…This information can be used to guide a discussion of law as a tool for combating HBV discrimination against students in accredited health professions programs. 12…”
Section: Mapping Studiesmentioning
confidence: 99%
“…10 A second mapping study that assessed the correspondence of CDC HIV testing guidelines and state laws found that no states had laws that would hinder compliance with CDC's 2006 revised HIV testing recommendations, but also that no state had laws enacting all relevant components for recommended HIV testing. 11 To illustrate the use of legal mapping to capture data on institutional policies, Moraras et al 12 collected data on policies related to the management of students with hepatitis B virus (HBV) infection from 83 Pennsylvania schools with accredited health professions programs. This information can be used to guide a discussion of law as a tool for combating HBV discrimination against students in accredited health professions programs.…”
Section: Mapping Studiesmentioning
confidence: 99%